BLENDED CPROT AS A CATALYST FOR DEVELOPING EFL TEACHERS’ PEDAGOGICAL COMPETENCIES - Yulia Nur Ekawati; Issy Yuliasri; Mursid Saleh; Rahayu Puji Haryanti (English Review: Journal of English Education, 2025)
Developing pedagogical competence among EFL pre-service teachers is essential for ensuring effective instruction in today’s communicative English classrooms. This study examines the effectiveness of the Blended Collaborative Peer Review of Teaching (B-CPRoT) model in enhancing the professional competencies of Indonesian pre-service teachers enrolled in a microteaching course. The model integrates face-to-face microteaching sessions with digital tools such as Elsakti and Google Meet, enabling structured cycles of observation, feedback, reflection, and revision. Grounded in Shian’s four-dimensional framework, the study compared two cohorts of English Education students, one implementing B-CPRoT and another following conventional microteaching without peer review. Quantitative data from performance-based assessments and paired-sample t-tests revealed that students who engaged in B-CPRoT showed significant improvements in teaching skills, classroom management, material presentation, and professional attitudes, particularly in teaching confidence and English fluency. Conversely, participants in the control group displayed stagnation and a slight performance decline. These findings underscore that B-CPRoT not only strengthens technical pedagogical abilities but also nurtures reflective and affective dimensions of teacher professionalism. The study concludes that structured, technology-supported peer review offers a sustainable framework for advancing EFL teacher education in blended learning contexts.